The Structure and Function of the Glycocalyx and Its Connection With Blood-Brain Barrier - Jin, Jing; Fang, Fuquan; Gao, Wei; Chen, Hanjian; Wen, Jiali; Wen, Xuehua; Chen, Junfa (Frontiers in Cellular Neuroscience, 2021)
The vascular endothelial glycocalyx is a dense, bush-like structure synthesized and secreted by endothelial cells, evenly distributed on the surface of the vascular endothelial cells. The blood-brain barrier structure is mainly composed of endothelial cells, glycocalyx, basement membranes, and astrocytes. The glycocalyx in the blood-brain barrier plays an indispensable role in many important physiological functions, including vascular permeability, inflammation, blood coagulation, and the synthesis of nitric oxide. Damage to the fragile glycocalyx can lead to increased permeability of the blood-brain barrier, tissue edema, glial cell activation, up-regulation of inflammatory chemokines, and ultimately brain tissue damage leading to increased mortality. In addition, more and more studies have confirmed that glycocalyx also mediates the pathogenesis of Alzheimer's disease. In this paper, combined with the literature on glycocalyx and cerebrovascular disease as well as Alzheimer's disease, the structure and function of glycocalyx in the blood-brain barrier and its relationship with Alzheimer's disease are discussed. It provides a theoretical basis for the diagnosis and treatment of neurological diseases, and highlights the value of glycocalyx in cerebrovascular research.